Services in the E-Banking as an Element Facilitate the Development of Information Society - Zakonnik, Łukasz; Karczmarz, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
In this article author presents the some interesting products in e-banks. Author tries to evaluate the impact of this products taking into consideration development of information society.